2022
DOI: 10.1021/acsomega.2c02237
|View full text |Cite
|
Sign up to set email alerts
|

Eryngium creticum L.: Chemical Characterization, SARS-CoV-2 Inhibitory Activity, and In Silico Study

Abstract: Phytochemical investigation of Eryngium creticum L. has resulted in isolation of five compounds, including four compounds that are reported from the plant for the first time. Compound 1 was identified as ( E )-rosmarinic acid, meanwhile, compound 2 was isolated as an ( E / Z )-rosmarinic acid mixture. Interestingly, the E / Z -is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Many studies have reported on the presence of different phenolic compounds in Eryngium extracts [ 25 , 26 , 27 , 28 ]. Our results are in agreement with the literature, which reported that among the phenolic compounds, rutin and sinapic acid were determined in E. planum , E. campestre, and E. maritimum extracts [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported on the presence of different phenolic compounds in Eryngium extracts [ 25 , 26 , 27 , 28 ]. Our results are in agreement with the literature, which reported that among the phenolic compounds, rutin and sinapic acid were determined in E. planum , E. campestre, and E. maritimum extracts [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…β -Sitosteryl glucoside ( 106 ) was isolated from A. strigosa [ 113 ]. Furthermore, a recent study reported the isolation of β -sitosterol ( 102 ) from E. criticum [ 149 ]. Figure 3 illustrates the chemical structure of the phytosterols identified in the selected genera.…”
Section: Resultsmentioning
confidence: 99%
“…Although the development of some vaccines against SARS-CoV-2 has raised expectations regarding the probable end of such unprecedented pandemic, the use of these vaccines has provoked concerns about some possible side effects and adverse interactions. , Besides, the capability of the said vaccines of complete disease prevention also remains to be witnessed, which underlines the importance of identifying new therapeutic agents with considerable efficacy and safety levels . During that journey, numerous studies have been introduced to stop the replication of SARS-CoV-2, focusing on a group of viral proteins as potential therapeutic targets, e.g., helicases, polymerases, and proteases, among others. , A large body of literature has therefore considered the application of virtual screening and molecular docking simulations as reasonable tools to mine for possible anti-SARS-CoV-2 candidates. , …”
Section: Resultsmentioning
confidence: 99%